The current issues and challenges in the management of floating knee injury: a retrospective study - Kenmegne, Guy Romeo; Zou, Chang; Lin, Yixiang; Yin, Yijie; Huang, Shengbo; Fang, Yue (Frontiers in Surgery, 2023)
Abstract Purpose: the management of floating knee injury is still controversial and challenging for trauma specialists. This study aimed to evaluate the incidence of floating knee in the lower limb trauma, analyzing the challenges in its management and factors affecting the clinical outcome. Methods: in this mono-center retrospective study, 36 consecutive patients were included. All individuals were diagnosed with ipsilateral fracture of femur and tibia, managed surgically according to their fracture pattern (Fraser classification) and the severity of the injury. The timing for the operation was determined based on the general condition of the patients and the local physiological condition of soft tissues. The patients clinical outcome were finally evaluated on the basis of their Karlstrom and Olerud scores and were categorized as excellent, good, acceptable, fair or poor. Results: in this study, the mean follow-up period was 51.39±16.02 months (11-130 months). The incidence of floating knee was 2.32% among lower limb trauma. Of the patients, there were 16 patients who suffered from floating knee injury in the left lower extremity, 18 in the right lower limb while in two patients the condition was bilateral. The most common injury mechanism was road traffic accident in 28 (77.78%) cases. The result of the follow-up revealed excellent to good result in 22 (61.11%) cases, acceptable result in two (5.56%) cases and fair to poor result in 12 (33.33%) cases according to the Karlström - Olerud scoring system; the most frequent early complications were wound infection, deep venous thrombosis in five (13.88%) of the cases while the most encountered late complication was common peroneal nerve palsy in two (5.56%) cases. Conclusion: the presence of important concomitant injuries to the floating knee together with the poor soft tissue condition constitute important factors influencing the management options hence leading to poor the clinical outcome.